FLEXURER SUBSIDENCE OF MAKASSAR STRAIT (Proceedings of the International Conference of Geological Engineering Faculty, 2022)
There were two types of hypothesis concerning formation of Makassar Strait and surrounding areas during the Tertiary periods  namely, compressive  and  extensional tectonics.  The compression   is  characterized by formation of Samarinda Anticlinorium  in East Kalimantan  and West Sulawesi Thrust Fold Belt in Sulawesi whereas the  extension was characterized by formation of aulacogen occupied by widening of Mouth of Mahakam River in Makasar Streat and also the presence of block faulting  and atenuation on pre Tertiary basement.This study on the basis of analysis  new surface and subsurface  data of those areas including DEM , Field data  and also seismics profiles suggest that  the sedimentation cycles and tectonic evolution in the area  were simultaneously   related to compressional tectonic  rather than the extensional tectonics and  form flexure subsidence activities.  The flexure subsidence itself  is related to loading  due to tectonic and  denudation  processes occured in the Tertiarry to Quarternary and this is usually generated during and post collisional activities.
Keywords: Makassar Strait; compression; extension; aulacogen; collision; denudation; flexure subsidence